Beyond lithium-ion: emerging frontiers in next-generation battery technologies - Vedhanarayanan, Balaraman; Seetha Lakshmi, K. C. (Frontiers in Batteries and Electrochemistry, 2024)
The rapid advancement of technology and the growing need for energy storage solutions have led to unprecedented research in the field of metal-ion batteries. This perspective article provides a detailed exploration of the latest developments and future directions in energy storage, particularly focusing on the promising alternatives to traditional lithium-ion batteries. With solidstate batteries, lithium-sulfur systems and other metal-ion (sodium, potassium, magnesium and calcium) batteries together with innovative chemistries, it is important to investigate these alternatives as we approach a new era in battery technology. The article examines recent breakthroughs, identifies underlying challenges, and discusses the significant impact of these new frontiers on various applicationsfrom portable electronics to electric vehicles and gridscale energy storage. Against the backdrop of a shifting paradigm in energy storage, where the limitations of conventional lithium-ion batteries are being addressed by cutting-edge innovations, this exploration offers insights into the transformative potential of next-generation battery technologies. The article further aims to contribute to the ongoing scientific dialogue by focusing on the environmental and economic implications of these technologies.